Retrospective review of a tertiary adult burn centre's experience with modified Meek grafting. Issue 1 (26th February 2016) - Munasinghe, Namal; Wasiak, Jason; Ives, Andrew; Cleland, Heather; Lo, Cheng Hean
Abstract: Background: Autologous split skin grafting is the gold standard in treating patients with massive burns. However, the limited availability of donor sites remains a problem. The aim of this study is to present our experience with the modified Meek technique of grafting, outcomes achieved and recommendations for optimized outcomes. Methods: We retrospectively reviewed patient records from our tertiary referral burn centre and the Bi-National Burns Registry to identify all patients who had modified Meek grafting between 2010 and 2013. Patient records were reviewed individually and information regarding patient demographics, mechanism of injury and surgical management was recorded. Outcome measures including graft take rate, requirement for further surgery and complications were also recorded. Results: Eleven patients had modified Meek grafting procedures. The average age of patients was 46 years old (range 23 – 64). The average total body surface area (TBSA) burnt was 56.75 % (range 20–80 %). On average, 87 % of the grafted areas healed well and did not require regrafting. In the regrafted areas, infection was the leading cause of graft failure. Conclusions: Modified Meek grafting is a useful method of skin expansion. Similar to any other grafting technique, infection needs to be sought and treated promptly. It is recommended for larger burns where donor sites are not adequate or where it is desirable to limit their extent.